2021
DOI: 10.2147/ijgm.s296125
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognosis of Abdominal or Thoracic Aortic Aneurysm Patients Admitted to Intensive Care Units After Surgical Treatment: A Multicenter Retrospective Observational Study

Abstract: Objective To investigate the characteristics and prognosis of abdominal or thoracic aortic aneurysm (AAA or TAA) patients admitted to intensive care unit (ICU) postoperatively. Methods Patients admitted to ICU postoperatively with a primary diagnosis of AAA or TAA were screened in the eICU Collaborative Research Database, which contained data from multiple ICUs throughout the continental United States in 2014 and 2015. Baseline characteristics and comorbidities and were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 29 publications
2
3
0
Order By: Relevance
“…In contrast, in another study conducted by Nicolini et al the mortality of aortic aneurysm was significantly higher in women than in men (17). In the study by Chen et al, the frequency of CAD was similar to the current research in patients with arterial aneurysms (14). In Wang et al's study, CAD and hypertension were identified as the primary risk factors for aortic aneurysm, aligning with the present study (8).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In contrast, in another study conducted by Nicolini et al the mortality of aortic aneurysm was significantly higher in women than in men (17). In the study by Chen et al, the frequency of CAD was similar to the current research in patients with arterial aneurysms (14). In Wang et al's study, CAD and hypertension were identified as the primary risk factors for aortic aneurysm, aligning with the present study (8).…”
Section: Discussionsupporting
confidence: 88%
“…Nonetheless, akin to Chen et al's study, the highest frequency was linked to abdominal aortic aneurysms. Chen et al's study also indicated that mortality rates differed based on the location of the aortic aneurysm (14). In the present study, the frequency of men surpassed that of women.…”
Section: Discussionsupporting
confidence: 56%
“…In our study, animals over six years old presented higher measurements in aortic and pulmonary diameters. In humans, the aortic diameter may increase with age, and collagen changes and systemic arterial hypertension may contribute to aortic artery aneurysm (Kobeissi et al 2019;Chen et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…5% of AA patients with multiorgan failure died before hospital discharge, which had higher incidence than the patients without organ dysfunction (23). The ICUmortality of AAA patients was 2.36%, while TAA patients had the incidence of 9.43% (24). When patients are in unstable situation after surgery, surgeons will routinely transfer them to ICU.…”
Section: Atmentioning
confidence: 99%